Manajemen Pemberian Pakan, Reproduksi dan Bonding pada Oposum Layang (Petaurus breviceps) di Penangkaran - Farida, Wartika Rosa; Sari, Andri Permata; Nugroho, Herjuno Ari; Sofyani, Umar (Universitas Sebelas Maret, 2016)
In order to nutritional needs of the sugar glider (Petaurus breviceps) in captivity, it has been given a Leadbeater modified feed and insects (superworm and crickets) as a natural food.Â The average feed intake of Leadbeater and fruits juice was 27.5 grams per head and superworm/crickets were 4 pieces per head per week. The nutritional content of feed modification Leadbeater 19% protein; 8.8% fat; 3.5% Ca; and 0.5% P. Each pairs of sugar glider placed in wire cages (60 cm x 40 cm x 40 cm) in order to facilitate the monitoring of reproduction. The mean increase in young birth of sugar gliders from March to October 2015 was 4.75 head per month. The bonding process is done since young sugar glider aged 2 months, in order to obtain young sugar glider as a product of pet animals